Review on national cuisine and regional cuisine / Nur Amalina Zulkifli and Nur Aina Zainal Abidin - Zulkifli, Nur Amalina; Zainal Abidin, Nur Aina (2017)
This research conducted was to review the regional cuisine and national cuisine in Malaysia. Nowadays individual perspective kept misunderstanding the basic difference between regional cuisine and national cuisine. The explanation towards regional was covered on the influence of this cuisine by the culture on certain destination and this further influence the acceptance towards the cuisine. The element of national cuisine is explained in this study. Moreover, this research focuses on the explanation towards the food that represents national cuisine.